2022
DOI: 10.2478/pjmpe-2022-0014
|View full text |Cite
|
Sign up to set email alerts
|

Automatic diagnosis of severity of COVID-19 patients using an ensemble of transfer learning models with convolutional neural networks in CT images

Abstract: Introduction: Quantification of lung involvement in COVID-19 using chest Computed tomography (CT) scan can help physicians to evaluate the progression of the disease or treatment response. This paper presents an automatic deep transfer learning ensemble based on pre-trained convolutional neural networks (CNNs) to determine the severity of COVID -19 as normal, mild, moderate, and severe based on the images of the lungs CT. Material and methods: In this study, two different deep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The study also revealed the importance of multi-modal data where the authors gathered the medical data from different sources including tomography and the X-ray images. Shalbaf et al [25] implemented 15 pre-trained deep learning models to automatically identify the COVID-19. These models are based on three well-known classification based architecture including Inception, ResNet, and DenseNet.…”
Section: B Contributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study also revealed the importance of multi-modal data where the authors gathered the medical data from different sources including tomography and the X-ray images. Shalbaf et al [25] implemented 15 pre-trained deep learning models to automatically identify the COVID-19. These models are based on three well-known classification based architecture including Inception, ResNet, and DenseNet.…”
Section: B Contributionsmentioning
confidence: 99%
“…The next experiments target validating the usability of the suggested ALMOST framework for disease detection. To reach this conclusion, intensive analysis has been carried out by comparing ALMOST with the baseline solutions InceptionResNet [23], and DenseNet [25]). The detailed results with complete explanation will be shown in the following.…”
Section: ) Mutation Ratementioning
confidence: 99%
“…Artificial intelligence (AI) methods, particularly deep learning models, have brought about ultrasound imaging by automating image processing and enabling the automated diagnosis of disease and detection of abnormalities. Convolutional neural networks (CNNs) have played a vital role in this transformation, demonstrating improvements in various medical imaging modalities [ 4 , 5 , 6 , 7 , 8 , 9 ]. However, the limitations of CNNs in capturing long-range dependencies and contextual information led to the development of vision transformers (ViTs) [ 10 ] in image processing.…”
Section: Introductionmentioning
confidence: 99%